Effects of Physical Exercise on Indicators of Inflammation Risk of the Gaster in a Male Wistar Rat Aging Model Created with D-galactose Induction - Murwaningsih, Dian; Meliala, Andreanyta; Sofro, Zaenal M (Makara Journal of Health Research, 2018)
Background: Physical exercise is a non-pharmacological treatment for various diseases. Aging is associated with deteriorating physiological function, and elderly individuals generally have inflammation or infection in the digestive tract. This study aimed to examine the effects of mild and moderate physical exercise intensities on the indicators of inflammation risk of the gaster in a male Wistar rat aging model created with D-galactose induction. Methods: This experimental research study had a post-test-only group design. The study included 24 3-month-old male Wistar rats weighing 200-300 g. The rats were equally divided into four groups (saline,+light-intensity physical exercise, and D-galactose+moderate-intensity physical exercise)D-galactose, D-galactose. D-galactose was continuously administered at 300 mg/ml/kg body weight. The study period was four weeks. The number of fibrocytes, mucosal thickness, and the number and size of mucosal glands were analyzed. Results: D-galactose induction triggered aging. Physical exercise had an effect on weight gain and decreased the number of fibrocytes. However, there were no effects on mucosal thickness and the number and size of mucosal glands. Conclusions: Physical exercise of mild/moderate intensity had an effect on the number of fibrocytes but did not have impact on the mucosal thickness or the number and size of mucosal glands.